2009
DOI: 10.1039/b908645e
|View full text |Cite
|
Sign up to set email alerts
|

Systematic evaluation of a strontium-specific extraction chromatographic resin for obtaining a purified Sr fraction with quantitative recovery from complex and Ca-rich matrices

Abstract: This paper presents a systematic evaluation of a commercially available strontium-specific extraction chromatographic resin based on a crown ether (Sr specÔ), for use in applications of Sr isotope ratio analysis dealing with samples displaying a complex and/or Ca-rich matrix composition. A protocol, consisting of (i) loading a sample digest in 7 M HNO 3 onto the resin, (ii) rinsing the resin with 7 M HNO 3 to remove concomitant matrix elements and (iii) rinsing the resin with 0.05 M HNO 3 to strip off the puri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
66
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 111 publications
(75 citation statements)
references
References 42 publications
6
66
1
2
Order By: Relevance
“…The 87 Rb/ 86 Sr ratios were calculated 204 following the procedures described by Vanhaecke et al (1999). 205 Sr was subsequently isolated from the sample matrix using a Sr-selective resin (Sr spec™), following 206 the extraction chromatography procedure described in detail by De Muynck et al (2009). Sr isotopic 207 measurements were performed using a Thermo Scientific Neptune MC-ICP-MS instrument.…”
Section: Figure 2: (A) Map View Of Budakalász Travertines (Modified Gmentioning
confidence: 99%
“…The 87 Rb/ 86 Sr ratios were calculated 204 following the procedures described by Vanhaecke et al (1999). 205 Sr was subsequently isolated from the sample matrix using a Sr-selective resin (Sr spec™), following 206 the extraction chromatography procedure described in detail by De Muynck et al (2009). Sr isotopic 207 measurements were performed using a Thermo Scientific Neptune MC-ICP-MS instrument.…”
Section: Figure 2: (A) Map View Of Budakalász Travertines (Modified Gmentioning
confidence: 99%
“…Sr isolation the protocol developed by De Muynck et al 12 was largely followed. The procedure for Pb isolation was based on the method from Deniel and Pin 17 , focusing on whether omitting and/or reducing cleaning steps could reduce laboratory time and costs, without compromising accuracy and precision of the data.…”
Section: Reagents and Materialsmentioning
confidence: 99%
“…De Muynck et al 12 already reported that no Sr isotopic fractionation occurs during the Sr isolation process using Sr spec TM resin. To assess potential isotopic fractionation of Pb during the isolation process and to obtain the elution profile of the Pb fraction, the 4 mL of 8 M HCl were collected in 10 aliquots of 400 µL each (see Table 1), that were afterwards analysed for their Pb concentration and Pb isotopic composition.…”
Section: Pb Isotopic Fractionation Introduced By the Isolation Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 0.2 g of bone powder was transferred to PTFE vessels and digested in 5 ml of subboiled HNO 3 and 3 ml of Suprapur H 2 O 2 30% using an Ethos 1 Milestone microwave oven. Subsequently, the isolation of strontium was performed with a strontium-specific extraction chromatographic resin following the protocol described by De Muynck et al (2009). Finally, strontium isotope ratio measurements were carried out via inductively coupled plasma mass spectrometry using a multicollector instrument housed at the University of Oviedo (Thermo Electron Corporation …”
Section: Strontium Isotope Analysis Methodology Bonesmentioning
confidence: 99%